Sources and structure of strategic innovation in construction companies considering smart management principles and sustainable development concept - Petrukha, N.M.; Dolhopolov, V.Y.; Mykytchenko, B.A.; Mukhin, A. A. (Ways to Improve Construction Efficiency, 2024)
The article is dedicated to the study of the sources and structure of strategic innovations in construction companies, considering the principles of SMART management and the concept of sustainable development. In the current context of globalization and technological transformation, the construction sector faces the need to adapt to dynamic changes, which increases the interest in innovative strategies. The implementation of cutting-edge technologies, digital solutions, and environmentally oriented approaches contributes to the enhancement of company competitiveness and ensures long-term economic growth. The study identifies the key sources of strategic innovations in construction, including technological (Industry 4.0, Building Information Modeling (BIM), process automation and robotics), organizational (agile project management methodologies, Lean Construction), environmental (energy-efficient technologies, use of renewable materials, green building certification), and socio-economic (investment in human capital, expanding partnership ecosystems, corporate social responsibility). Special attention is given to the principles of SMART management, which involve the use of digital technologies and analytics to improve management efficiency. In particular, the role of big data (Big Data), artificial intelligence (AI), and the Internet of Things (IoT) in decision-making processes is examined, allowing companies to significantly reduce costs, improve productivity, and enhance the quality of construction products. The article explores the interconnection between strategic innovations and the concept of sustainable development. It is proven that the integration of ESG (Environmental, Social, and Governance) principles contributes to the formation of environmentally safe and socially responsible business models in construction. The implementation of circular economy practices, waste minimization, use of renewable energy sources, and the introduction of smart urban planning are essential elements of the industry's innovative development. Based on the conducted analysis, a conceptual model of strategic innovations in construction companies is developed, which combines technological, environmental, and managerial solutions. The proposed methodological approaches can be used to develop effective strategies for the long-term development of construction enterprises.